Effects of chocolate/cocoa on body health and diabetes: A narrative review - Javad Yaghmoorian-Khojini; Niloofar Eftekhari; Kamran Ghaedi; Reza Ghiasvand (Fiyz̤, 2022)
Background: Cocoa and dark chocolate contain polyphenols and several other positive components, and diets containing balanced amounts of these substances have beneficial effects on human health. In this review article provided a comprehensive and fruitful explanations about cocoa and chocolate as a world popular food, their positive and constructive properties in the physiological processes of the body, especially diabetes. Materials and Methods: In this study has been used the method of library collection, search in various texts and valid scientific articles. Results: Overall, balanced consumption of appropriate doses of cocoa and chocolate, especially dark chocolate, in addition to slowing the progression of diabetes and its preventive effects, contains many other positive effects, include increasing the potential to prevent cardiovascular disease and increasing the efficiency and capacity of the heart and kidneys, increasing endorphins and delivering it to the brain and increasing the body's sense of pleasure and energy, improving digestion. As a result, they help improve gastrointestinal function, increase good cholesterol (HDL) and decrease bad cholesterol (LDL), and have anti-inflammatory and anti-cancer properties. Conclusion: Consumption of chocolate, especially dark type, if it is appropriate, due to its beneficial components such as flavanols, can have positive effects on many body processes, especially blood sugar control, and prevent diabetes.